A method for synthesizing 1,5-pentanediol by hydrolysis of furfuryl alcohol

CN122958244APending Publication Date: 2026-10-23CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510482971.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-17
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0006]本发明的目的是为了克服现有技术存在的糠醇氢解反应成本高和目标产物1,5-戊二醇选择性低问题,提供一种糠醇氢解合成1,5-戊二醇的方法,该方法能够提高产物1,5-戊二醇选择性

Benefits of technology

[0011]本发明提供的方法,选用非贵金属催化剂作为氢解催化剂,生产成本低;通过引入稀土金属氧化物作为载体,能够改善活性金属的分散性,活性金属与载体紧密接触,有利于反应原料糠醇的吸附;选择活性金属0价物种和2价物种的比值在特定范围内的氢解催化剂,有利于氢气的活化及糠醇的吸附活化,提高产物1,5-戊二醇的选择性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958244A_ABST
    Figure CN122958244A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of furfuryl alcohol hydrogenolysis, and discloses a method for synthesizing 1,5-pentanediol through furfuryl alcohol hydrogenolysis. The method for synthesizing 1,5-pentanediol through furfuryl alcohol hydrogenolysis comprises the following steps: contacting reaction raw material furfuryl alcohol and a hydrogenolysis catalyst in the presence of hydrogen to perform a hydrogenolysis reaction; the hydrogenolysis catalyst comprises a carrier and an active metal, the carrier is selected from at least one of Pr6O 11 , La2O3, CeO2 and Y2O3, and the active metal is selected from at least one of Cu, Co and Ni; after the hydrogenolysis catalyst is reduced at 400 DEG C for 2h, the ratio of 0-valence species and 2-valence species of the active metal is 0.1-2 through XPS characterization. The method can improve the selectivity of the product 1,5-pentanediol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of furfuryl alcohol hydrogenolysis, and specifically to a method for synthesizing 1,5-pentanediol by furfuryl alcohol hydrogenolysis. Background Technology

[0002] Due to global economic growth, dwindling fossil fuel reserves, and environmental issues, researchers are increasingly focusing on the development and utilization of renewable resources. Biomass, being widely available, inexpensive, and renewable, is essential for effectively converting into fuels or high-value-added chemicals to address growing energy and environmental problems. Furfuryl alcohol (FFA) is a popular C5 compound. Based on its active carbon-carbon double bonds and hydroxyl groups, catalytic hydrogenation can convert it into a series of high-value-added chemicals, such as tetrahydrofurfuryl alcohol (THFA), 1,2-pentanediol, and 1,5-pentanediol. 1,5-pentanediol is primarily used in the production of polyester resins, polyester polyols, and polyurethane foams.

[0003] Tomishige et al. in Japan first reported a one-step hydrogenolysis method for preparing 1,5-pentanediol from tetrahydrofurfuryl alcohol, achieving a conversion rate of over 90% and a selectivity of over 90% for 1,5-pentanediol, representing the highest reported yield to date (Chem. Commun., 2009, 2035 2037; Journal of Catalysis, 2009, 267, 89-92; Journal of Catalysis, 2012, 294, 171-183). However, the catalysts used were expensive Rh or Ir-based catalysts, resulting in high production costs and requiring high pressure for hydrogenolysis ring-opening.

[0004] Chinese patent application CN114073967A discloses a NiPt / WO3-Al2O3 catalyst. The reaction temperature is initially set at 100℃ for 5 hours, then increased to 160℃ for 15 hours, under a pressure of 3 MPa, achieving a 1,5-pentanediol yield of 96.2%. This is the first report on the catalytic conversion of furfural to 1,5-pentanediol using a supported Ni alloy nanocatalyst. Although this method produces few byproducts and exhibits high selectivity, the catalyst suffers from poor aqueous-phase stability, hindering large-scale application.

[0005] It is evident that the cost of existing catalysts remains high, and there is still room for improvement in the selectivity and yield of the product 1,5-pentanediol. Summary of the Invention

[0006] The purpose of this invention is to overcome the problems of high cost and low selectivity of the target product 1,5-pentanediol in the existing technology of furfuryl alcohol hydrogenolysis reaction, and to provide a method for synthesizing 1,5-pentanediol by furfuryl alcohol hydrogenolysis, which can improve the selectivity of the product 1,5-pentanediol.

[0007] To achieve the above objectives, the present invention provides a method for the hydrogenolysis synthesis of 1,5-pentanediol from furfuryl alcohol, wherein the method comprises: in the presence of hydrogen, contacting the reactant furfuryl alcohol and a hydrogenolysis catalyst to carry out a hydrogenolysis reaction;

[0008] The hydrogenolysis catalyst comprises a support and an active metal, wherein the support is selected from Pr6O. 11 At least one of La2O3, CeO2 and Y2O3, wherein the active metal is selected from at least one of Cu, Co and Ni;

[0009] After the hydrogenolysis catalyst was reduced at 400℃ for 2 hours, XPS characterization showed that the ratio of 0-valent to 2-valent species of the active metal was 0.1-2.

[0010] Preferably, after the hydrogenolysis catalyst is reduced at 400°C for 2 hours, the ratio of 0-valent species to divalent species of the active metal is 0.5-1.8, more preferably 1.1-1.3, as determined by XPS characterization.

[0011] The method provided by this invention uses a non-precious metal catalyst as the hydrogenolysis catalyst, resulting in low production costs. By introducing rare earth metal oxides as a support, the dispersibility of the active metal can be improved, and the active metal is in close contact with the support, which is beneficial to the adsorption of furfuryl alcohol as a reactant. Selecting a hydrogenolysis catalyst with a ratio of 0-valent to 2-valent species of the active metal within a specific range is beneficial to the activation of hydrogen and the adsorption activation of furfuryl alcohol, thereby improving the selectivity of the product 1,5-pentanediol. Attached Figure Description

[0012] Figure 1 To prepare Example 2 45% Ni / Pr6O 11 XPS spectra of catalyst (45Ni-Pr) reduced at -700℃.

[0013] Figure 2 To prepare Example 2 45% Ni / Pr6O 11 XRD, H2-TPR and CO2-TPD characterization results of the catalyst prepared at -700℃ (45Ni-Pr), the comparative example of 345% Ni / MgO at -700℃ (45Ni-Mg), and the comparative example of 445% Ni / Al2O3 at -700℃ (45Ni-Al);

[0014] Figure 2 -(a) is the preparation example 2 45% Ni / Pr6O11 XRD characterization results of the catalyst (45Ni-Pr) at -700℃, the comparative example 3 (45% Ni / MgO) at -700℃ (45Ni-Mg), and the comparative example 4 (45% Ni / Al2O3) at -700℃ (45Ni-Al);

[0015] Figure 2 -(b) is for the preparation of 45% Ni / Pr6O in Example 2 11 XRD characterization results of the catalyst (45Ni-Pr) at -700℃, the comparative example 3 45% Ni / MgO at -700℃ (45Ni-Mg), and the comparative example 445% Ni / Al2O3 at -700℃ (45Ni-Al) after reduction;

[0016] Figure 2 -(c) is the preparation of Example 2 45% Ni / Pr6O 11 H2-TPR characterization of the catalyst (45Ni-Pr) at -700℃, the comparative example 3 (45% Ni / MgO) at -700℃ (45Ni-Mg), and the comparative example 4 (45% Ni / Al2O3) at -700℃ (45Ni-Al).

[0017] Figure 2 -(d) is the preparation of Example 2 45% Ni / Pr6O 11 CO2-TPD characterization of the catalyst at -700℃ (45Ni-Pr), the comparative example 3 45% Ni / MgO at -700℃ (45Ni-Mg), and the comparative example 445% Ni / Al2O3 at -700℃ (45Ni-Al) after reduction.

[0018] Figure 3 45% Ni / Pr6O 11 Kinetic behavior curves of furfuryl alcohol hydrogenolysis of the catalyst (45Ni-Pr) at -700℃, the comparative example of 345% Ni / MgO at -700℃ (45Ni-Mg), and the comparative example of 445% Ni / Al2O3 at -700℃ (45Ni-Al);

[0019] Figure 3 -(a) is the preparation example 2 45% Ni / Pr6O 11 Catalyst (45Ni-Pr) -700℃;

[0020] Figure 3 -(b) Preparation of Comparative Example 3 45% Ni / MgO-700℃ catalyst (45Ni-Mg);

[0021] Figure 3-(c) is for the preparation of comparative example 4 45% Ni / Al2O3-700℃ catalyst (45Ni-Al).

[0022] Figure 4 45% Ni / Pr6O 11 TEM and HRTEM characterization images of the catalyst (45Ni-Pr) at -700℃, the comparative example of 345% Ni / MgO at -700℃ (45Ni-Mg), and the comparative example of 445% Ni / Al2O3 at -700℃ (45Ni-Al) after reduction;

[0023] Figure 4 -(a) TEM characterization of the comparative example 4 45% Ni / Al2O3-700℃ catalyst (45Ni-Al);

[0024] Figure 4 -(b) is a TEM characterization image of the comparative example 3 45% Ni / MgO-700℃ catalyst (45Ni-Mg);

[0025] Figure 4 -(c) is the preparation of Example 2 45% Ni / Pr6O 11 TEM characterization of the catalyst (45Ni-Pr) at -700℃;

[0026] Figure 4 -(d) is the HRTEM characterization diagram of the comparative example 4 45% Ni / Al2O3-700℃ catalyst (45Ni-Al);

[0027] Figure 4 -(e) is the HRTEM characterization diagram of the comparative example 3 45% Ni / MgO-700℃ catalyst (45Ni-Mg);

[0028] Figure 4 -(f) is the preparation example 2 45% Ni / Pr6O 11 HRTEM characterization of the catalyst (45Ni-Pr) at -700℃.

[0029] Figure 5 To prepare Example 2 45% Ni / Pr6O 11 BET characterization results of the catalyst (45Ni-Pr) at -700℃, the comparative example 3 (45% Ni / MgO) at -700℃ (45Ni-Mg), and the comparative example 4 (45% Ni / Al2O3) at -700℃ (45Ni-Al);

[0030] Figure 5 -(a) is 45%Ni / Pr6O 11N2- adsorption-desorption isotherms of the catalyst (45Ni-Pr) at -700℃, the catalyst (45Ni-Mg) prepared by comparative example 3 (45% Ni / MgO) at -700℃, and the catalyst (45Ni-Al) prepared by comparative example 4 (45% Ni / Al2O3) at -700℃.

[0031] Figure 5 -(b) is 45% Ni / Pr6O 11 BJH pore size distribution diagrams of the catalyst at -700℃ (45Ni-Pr), the comparative example 3 (45% Ni / MgO) at -700℃ (45Ni-Mg), and the comparative example 4 (45% Ni / Al2O3) at -700℃ (45Ni-Al).

[0032] Figure 6 To prepare Example 2 45% Ni / Pr6O 11 HAADF-STEM-EDX elemental analysis scans of the catalyst (45Ni-Pr) at -700℃, the catalyst (45Ni-Mg) prepared by comparative example 3 (45% Ni / MgO) at -700℃, and the catalyst (45Ni-Al) prepared by comparative example 4 (45% Ni / Al2O3) at -700℃ after reduction;

[0033] Figure 6 -(a) is the preparation example 2 45% Ni / Pr6O 11 Catalyst (45Ni-Pr) -700℃;

[0034] Figure 6 -(b) is for the preparation of comparative example 4 45% Ni / Al2O3 catalyst (45Ni-Al) at 700℃;

[0035] Figure 6 -(c) is for the preparation of Comparative Example 3 45% Ni / MgO-700℃ catalyst (45Ni-Mg). Detailed Implementation

[0036] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0037] This invention provides a method for synthesizing 1,5-pentanediol by hydrogenolysis of furfuryl alcohol, wherein the method comprises: in the presence of hydrogen, contacting the reactant furfuryl alcohol and a hydrogenolysis catalyst to carry out a hydrogenolysis reaction;

[0038] The hydrogenolysis catalyst comprises a support and an active metal, wherein the support is selected from Pr6O. 11 At least one of La2O3, CeO2 and Y2O3, wherein the active metal is selected from at least one of Cu, Co and Ni;

[0039] After the hydrogenolysis catalyst was reduced at 400℃ for 2 hours, XPS characterization showed that the ratio of 0-valent to 2-valent species of the active metal was 0.1-2.

[0040] The method provided by this invention uses a non-precious metal catalyst as the hydrogenolysis catalyst, resulting in low production costs. By introducing rare earth metal oxides as a support, the dispersibility of the active metal can be improved, and the active metal is in close contact with the support, which is beneficial to the adsorption of furfuryl alcohol as a reactant. Furthermore, selecting a hydrogenolysis catalyst with a ratio of 0-valent to 2-valent active metal species within a specific range is beneficial to the activation of hydrogen and the adsorption activation of furfuryl alcohol, thereby improving the selectivity of the product 1,5-pentanediol.

[0041] In this invention, preferably, after the hydrogenolysis catalyst is reduced at 400°C for 2 hours, XPS characterization shows that the ratio of 0-valent to divalent species of the active metal is 0.5-1.8, more preferably 1.1-1.3. The advantage of this preferred embodiment is that selecting a hydrogenolysis catalyst with a ratio of 0-valent to divalent species of the active metal within a specific range facilitates the activation of hydrogen and the adsorption activation of furfuryl alcohol, thereby improving the selectivity of the target product.

[0042] In this invention, a Thermo Fisher Scientific Escalab 250xi X-ray photoelectron spectrometer (XPS) was used with Al Kα radiation (1486.6 eV) as the incident beam to characterize the surface chemical state of Ni and Pr on the catalyst surface. Before sample analysis, the sample was placed in the spectrometer's reactor and reduced in situ at 400°C for 2 hours by purging with hydrogen gas. The C1s peak at 284.8 eV was used as a reference to calibrate all binding energies (BEs). Spectral fitting and peak integration were performed using Avantage software. Based on the peak areas of the integrated active metal 0-valent and divalent species, the ratio of active metal 0-valent to divalent species was calculated.

[0043] In this invention, preferably, the total amount of the strong base and the weak base in the hydrogenolysis catalyst accounts for 85-100% of the total base content, more preferably 94-96%. The advantage of this preferred embodiment is that the proportion of the strong base and the weak base within a certain range is beneficial for furfuryl alcohol adsorption; when the total amount of the strong base and the weak base is lower or higher than the above range, it is not conducive to furfuryl alcohol adsorption, and the selectivity of the target product is poor.

[0044] In this invention, carbon dioxide temperature-programmed desorption (CO2-TPD) is performed on a Micromeritics Autochem II chemisorption analyzer equipped with a thermal conductivity detector (TCD) to characterize the surface alkalinity of the sample. In a typical procedure, 100 mg of sample is pretreated in a flowing stream of 10 vol% H2-Ar gas (30 mL / min) at 400 °C for 2 hours, and then cooled to 60 °C in a flowing stream of He (99.999%, 30 mL / min). At this temperature, CO2 was adsorbed onto the catalyst for 30 minutes under a 10 vol% CO2-He gas (30 mL / min) until saturation. Then, the temperature was raised to 100 °C to remove the physically adsorbed CO2. Finally, CO2-TPD curves were obtained from 100 °C to 800 °C in a He gas stream (99.999%, 30 mL / min) at a heating rate of 10 °C / min. The range of 100-250 °C represents a weak base, 250-400 °C a medium-strong base, and 400-800 °C a strong base.

[0045] In this invention, based on the total weight of the hydrogenolysis catalyst, the content of the support is 55-90%, and the content of the active metal (calculated as an element) is 10-45%. Preferably, based on the total weight of the hydrogenolysis catalyst, the content of the support is 55-70%, and the content of the active metal (calculated as an element) is 30-45%.

[0046] In this invention, the loading of active metals in the catalyst was determined using Thermo Elemental Iris Intrepid II XSP inductively coupled plasma optical emission spectrometry (ICP-OES).

[0047] In this invention, preferably, the carrier is Pr6O 11 The advantage of this preferred embodiment is that Pr6O 11 The introduction of [a specific substance] can improve the dispersion of active metals, enhance the concentration of weak and moderately strong basic sites and oxygen vacancies on the catalyst surface, which is beneficial to the adsorption of furfuryl alcohol and improves the selectivity of the target product.

[0048] In this invention, preferably, the active metal is Ni. The advantage of this preferred embodiment is that furfuryl alcohol can be rapidly hydrogenated to tetrahydrofurfuryl alcohol under the action of 0-valent Ni. The synergistic effect of Ni and the support allows tetrahydrofurfuryl alcohol to undergo further ring-opening hydrogenolysis to generate 1,5-pentanediol, improving the selectivity of 1,5-pentanediol. In contrast, Cu and Co directly open the furan ring of furfuryl alcohol, resulting in lower selectivity for 1,5-pentanediol.

[0049] In this invention, the preparation method of the hydrogenolysis catalyst is not particularly limited. According to a preferred embodiment of the present invention, the preparation method of the hydrogenolysis catalyst includes the following steps:

[0050] (1) Mix the active metal precursor, the carrier precursor and the template agent, and carry out a sol-gel reaction to obtain a gel material;

[0051] (2) The gel material described in step (1) is dried and calcined. The calcination includes a first-stage calcination and a second-stage calcination. The temperature of the first-stage calcination is 300-600℃, and the temperature of the second-stage calcination is 600-900℃.

[0052] The inventors of this invention discovered in their research that by employing a sol-gel method combined with a two-stage calcination process, and by controlling the two-stage calcination temperature to below 900°C, the content of weak and moderately strong basic sites on the catalyst surface can be further optimized, thereby improving the selectivity of the product 1,5-pentanediol; moreover, the preparation process is simple, there is no secondary pollution during the preparation process, and the production cost is low.

[0053] In this invention, the type of active metal precursor is not particularly limited, as long as the required active metal element can be provided. Preferably, in step (1), the active metal precursor is selected from salts of various active metals, and more preferably from at least one of nitrates, basic carbonates, sulfates and chlorides of various active metals, such as nickel nitrate, copper nitrate, cobalt nitrate, basic nickel carbonate, basic cobalt carbonate, nickel chloride, copper chloride, etc.

[0054] In this invention, the type of carrier precursor is not particularly limited, as long as it can provide the metal element required in the carrier. Preferably, in step (1), the carrier precursor is selected from the metal salts of each carrier, and more preferably from at least one of the nitrates, basic carbonates, sulfates and chlorides of each carrier, such as praseodymium nitrate, lanthanum nitrate, cerium nitrate, yttrium nitrate, etc.

[0055] In this invention, preferably, in step (1), the template agent includes a first template agent and a second template agent.

[0056] In this invention, the type of the first template agent is not particularly limited. Preferably, the first template agent is an organic acid and / or an inorganic acid, and is preferably selected from at least one of tartaric acid, acetic acid, and citric acid.

[0057] In this invention, the type of the second template agent is not particularly limited. Preferably, the second template agent is a carbohydrate compound, and more preferably selected from at least one of fructose, sucrose, and glucose.

[0058] In this invention, preferably, the molar ratio of the first template agent to the active metal precursor is 0.1-5:1, more preferably 0.5-3:1.

[0059] In this invention, preferably, the molar ratio of the second template agent to the active metal precursor is 0.1-5:1, more preferably 0.5-3:1.

[0060] In this invention, there is no particular limitation on the mixing order of the materials in step (1). According to a specific embodiment of the present invention, step (1) includes:

[0061] (1-1) The active metal precursor and the carrier precursor are first mixed to obtain mixture I;

[0062] (1-2) The first template agent and mixture I are mixed a second time to obtain mixture II;

[0063] (1-3) The second template agent and mixture II are mixed for the third time, and then a sol-gel reaction is carried out to obtain a gel material.

[0064] In this invention, the method of the first mixing is not particularly limited; for example, it can be carried out under stirring conditions. In this invention, the conditions for the first mixing are not particularly limited; preferably, the first mixing time is 10-50 minutes.

[0065] In this invention, the methods of the second and third mixing are not particularly limited; for example, they can be carried out under stirring conditions. The conditions for the second and third mixing are not particularly limited; preferably, the total time for the second and third mixing is 10-270 minutes. The time for the second and third mixing is not particularly limited, as long as the total time is satisfied.

[0066] In this invention, preferably, in step (1), the conditions for the sol-gel reaction include: a temperature of 70-98°C and a time of 0.5-2h.

[0067] In this invention, the drying conditions in step (2) are not particularly limited. Preferably, the drying conditions in step (2) include: a drying temperature of 90-140°C and a drying time of 5-24 hours.

[0068] In this invention, preferably, in step (2), the conditions for the first-stage roasting include: the roasting temperature is 300-500℃, the time is 1-6h, and the heating rate is 2-7℃ / min.

[0069] In this invention, preferably, in step (2), the conditions for the two-stage calcination include: the temperature of the two-stage calcination is 650-730℃, the time is 3-7h, and the heating rate is 2-7℃ / min.

[0070] The inventors of this invention discovered in their research that by employing a sol-gel method combined with a two-stage calcination process, and preferably controlling the second-stage calcination temperature to below 730°C, the content of weak and moderately strong basic sites on the catalyst surface can be further optimized, thereby improving the selectivity of the product 1,5-pentanediol; moreover, the preparation process is simple, there is no secondary pollution during the preparation process, and the production cost is low.

[0071] In this invention, the selection range of conditions for the hydrogenolysis reaction is relatively wide. Preferably, the conditions for the hydrogenolysis reaction include: a reaction temperature of 140-210℃, a reaction hydrogen pressure of 4-7 MPa, a reaction time of 2-72 h, and the amount of the hydrogenolysis catalyst used is 0.2-1 g compared to 1 g of furfuryl alcohol as a reactant. Preferably, the conditions for the hydrogenolysis reaction include: a reaction temperature of 150-190℃, a reaction hydrogen pressure of 5-7 MPa, a reaction time of 48-72 h, and the amount of the hydrogenolysis catalyst used is 0.3-0.5 g compared to 1 g of furfuryl alcohol as a reactant.

[0072] In this invention, preferably, the hydrogenolysis reaction further includes being carried out in the presence of a solvent.

[0073] In this invention, the type of solvent is not particularly limited. Preferably, the solvent is selected from at least one of isopropanol, ethanol, and 1,4-dioxane.

[0074] In this invention, preferably, the amount of solvent used is 10-100g compared to 1g of furfuryl alcohol, a reactant.

[0075] In this invention, preferably, the hydrogenolysis reaction further includes: reducing the hydrogenolysis catalyst before the hydrogenolysis reaction.

[0076] In this invention, preferably, the reduction reaction is carried out in a hydrogen-containing atmosphere, and more preferably in hydrogen gas.

[0077] In this invention, the conditions for the reduction treatment are not particularly limited. Preferably, the conditions for the reduction treatment include: a temperature of 300-500℃ and a time of 1-4 hours.

[0078] The present invention will be described in detail below through embodiments.

[0079] Unless otherwise specified, all raw materials used in the following examples and comparative examples are commercially available products.

[0080] Unless otherwise specified, all percentages in the following preparation examples, embodiments, and comparative examples are by weight.

[0081] Unless otherwise specified, room temperature in the following preparation examples, embodiments and comparative examples refers to 25±5℃.

[0082] In the following examples, 45% Ni / Pr6O11 The calculation process is illustrated as an example: With Pr(NO3)3·6H2O fixed at 0.015 mol, according to xNi / (xNiO+0.015 / 6Pr6O) 11 =0.45, calculate the required number of moles of Ni(NO3)2·6H2O, and calculate the amount of other active metals to be added according to this formula.

[0083] The X-ray diffraction (XRD) patterns of the hydrogenolysis catalyst were determined using a Bruker D8 Advance powder diffractometer equipped with Cu-Kα radiation.

[0084] The nitrogen adsorption-desorption isotherm of the hydrogenolysis catalyst was determined at -196 °C using a Quantachrome Autosorb-3B instrument. Prior to measurement, the sample was activated under vacuum at 300 °C for 6 hours. Specific surface area was calculated using the Brunauer-Emmett-Teller (BET) equation. Pore size distribution was calculated based on the desorption branch of the isotherm using the Barrett-Joyner-Halenda (BJH) method.

[0085] The loading of active metals in the hydrogenolysis catalyst was determined using a Thermo Elemental Iris Intrepid II XSP inductively coupled plasma optical emission spectrometer (ICP-OES).

[0086] Transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HRTEM), and elemental mapping of the hydrogenolysis catalyst after reduction at 400℃ for 2 hours were performed using a JEOL JEM-2100F microscope.

[0087] Hydrogen temperature-programmed reduction (H2-TPR) was performed on a Micromeritics Autochem II chemisorption analyzer equipped with a thermal conductivity detector (TCD). First, 100 mg of sample was treated with flowing He (99.999%, 30 mL / min) at 300 °C for 1 hour. After the sample cooled to room temperature, H2-TPR curves were obtained from 100 °C to 800 °C in flowing 10 v / min H2-Ar gas (30 mL / min) at a heating rate of 10 °C / min.

[0088] Temperature-programmed desorption (CO2-TPD) of carbon dioxide was performed on a Micromeritics Autochem II chemisorption analyzer equipped with a thermal conductivity detector (TCD) to characterize the surface basicity of the hydrogenolysis catalyst. In a typical procedure, 100 mg of sample was pretreated in a flowing stream of 10 vol% H2-Ar gas (30 mL / min) at 400 °C for 2 h, and then cooled to 60 °C in a flowing stream of He (99.999%, 30 mL / min). At this temperature, CO2 was adsorbed onto the catalyst for 30 minutes under a 10 vol% CO2-He gas (30 mL / min) until saturation. Then, the temperature was raised to 100 °C to remove the physically adsorbed CO2. Finally, CO2-TPD curves were obtained from 100 °C to 800 °C in a He gas stream (99.999%, 30 mL / min) at a heating rate of 10 °C / min. The range of 100-250 °C represents a weak base, 250-400 °C a medium-strong base, and 400-800 °C a strong base.

[0089] The surface chemical states of Ni and Pr on the catalyst surface were characterized using a Thermo Fisher Scientific Escalab 250xi X-ray photoelectron spectrometer (XPS) with Al Kα radiation (1486.6 eV) as the incident beam. Before analysis, the samples were placed in the spectrometer's reactor and reduced in situ at 400 °C for 2 h by purging with hydrogen. The C1s peak at 284.8 eV was used as a reference to calibrate all binding energies (BEs). Spectral fitting and peak integration were performed using Avantage software. Based on the peak areas of the integrated 0-valent and divalent active metal species, the ratio of 0-valent to divalent active metal species was calculated.

[0090] In this invention, the reduction treatment conditions are as follows: 0.15g of catalyst is reduced in a quartz tube under hydrogen gas, the hydrogen flow rate is 50mL / min, the reduction temperature is 400℃, and the reduction time is 2h.

[0091] Preparation Example 1

[0092] (1) According to Ni / (NiO+Pr6O 11 )= X Ni(NO3)2·6H2O and Pr(NO3)3·6H2O were dissolved in 20 mL of deionized water in a weight ratio of 1:1. Citric acid (metal salt (Ni+Pr) molar ratio of 1:1) was then added to the solution under continuous stirring. 10 g of glucose was then stirred at room temperature for 4.5 h. Excess water was evaporated in a 98 °C water bath for 0.8 h until a viscous gel was formed.

[0093] (2) The obtained gel was dried overnight at 120°C. Finally, the dried gel was calcined in an air atmosphere in a muffle furnace at a first-stage calcination temperature of 500°C (heating from room temperature to 500°C at a heating rate of 5°C / min) for 4 hours. Then, it was calcined in an air atmosphere in a muffle furnace at a second-stage calcination temperature of 700°C (heating from 500°C to the second-stage calcination temperature at a heating rate of 3.5°C / min) for another 5 hours. The hydrogenolysis catalyst obtained had the following composition: 20% Ni / Pr6O 11 -700℃.

[0094] Preparation of Comparative Example 1

[0095] Following the method of Preparation Example 1, using MgO as a support, the hydrogenolysis catalyst prepared had the following composition: 20% Ni / MgO - 700℃.

[0096] Preparation of Comparative Example 2

[0097] Following the method of Preparation Example 1, using Al2O3 as a support, the hydrogenolysis catalyst prepared had the following composition: 20% Ni / Al2O3-700℃.

[0098] Preparation Example 2

[0099] The method of preparation example 1 was followed, except that the composition of the hydrogenolysis catalyst was different. The hydrogenolysis catalyst obtained had the following composition: 45% Ni / Pr6O 11 -700℃, denoted as 45Ni-Pr.

[0100] Figure 1 To prepare Example 2 45% Ni / Pr6O 11 XPS spectra of the catalyst (45Ni-Pr) reduced at -700℃ for 2 hours at 400℃, from... Figure 1 It can be seen that at 45% Ni / Pr6O 11 The catalyst (45Ni-Pr) at -700℃ contains Pr 3+ Species (content 66.4%, with characteristic peaks at 928.2 eV and 933.1 eV) and Pr 4+ Species (content 33.6%, with characteristic peaks at 929.3 eV and 934.7 eV), high content of Pr 3+ It helps the adsorption of oxygen-containing groups in furfuryl alcohol and improves the selectivity of the product.

[0101] Preparation of Comparative Example 3

[0102] The method of Preparation Example 2 is the same, except that MgO is used as the support and the two-stage calcination temperature is 700℃. The hydrogenolysis catalyst obtained has the following composition: 45% Ni / MgO-700℃, denoted as 45Ni-Mg.

[0103] Preparation of Comparative Example 4

[0104] The method of Preparation Example 2 is the same, except that Al2O3 is used as the support and the two-stage calcination temperature is 700℃. The hydrogenolysis catalyst obtained has the following composition: 45% Ni / Al2O3-700℃ (45Ni-Al).

[0105] Figure 2 To prepare Example 2 45% Ni / Pr6O 11 XRD, H2-TPR, and CO2-TPD characterization results of the catalyst prepared at -700℃ (45Ni-Pr), the comparative example 3 (45% Ni / MgO-700℃ catalyst, 45Ni-Mg), and the comparative example 4 (45% Ni / Al2O3-700℃ catalyst, 45Ni-Al).

[0106] Figure 2 -(a) is the preparation example 2 45% Ni / Pr6O 11 XRD patterns of the catalyst prepared at -700℃ (45Ni-Pr), the comparative example 3 (45% Ni / MgO) catalyst prepared at -700℃ (45Ni-Mg), and the comparative example 4 (45% Ni / Al2O3) catalyst prepared at -700℃ (45Ni-Al), from... Figure 2 As can be seen from (a), in Preparation Example 2, 45% Ni / Pr6O 11 The catalyst (45Ni-Pr) at -700℃ exhibited diffraction peaks at 2θ = 28.2°, 32.7°, 37.2°, 43.3°, 47.0°, 55.7°, 62.9°, 68.6°, 75.4°, 79.4°, and 87.3°, indicating the presence of NiO and Pr6O phases in the catalyst. 11 The preparation of Comparative Example 3, a 45% Ni / MgO catalyst at 700℃ (45Ni-Mg), showed diffraction peaks at 2θ = 37°, 43.1°, 62.6°, 75.1°, and 79.1°, indicating the presence of NiMgO2 solid solution in the catalyst. The preparation of Comparative Example 4, a 45% Ni / Al2O3 catalyst at 700℃ (45Ni-Al), showed diffraction peaks at 2θ = 19.1°, 37.2°, 43.3°, 45°, 62.9°, 65.5°, 75.4°, and 79.4°, indicating the presence of NiO and spinel NiAl2O4 phases in the catalyst.

[0107] Figure 2 -(b) is for the preparation of 45% Ni / Pr6O in Example 2 11 XRD patterns of the catalyst (45Ni-Pr) prepared at -700℃, the comparative example 3 (45% Ni / MgO) prepared at -700℃, the comparative example 4 (45% Ni / Al2O3) prepared at -700℃, and the comparative example 4 (45% Ni / Al2O3) prepared at -700℃, after reduction at 400℃ for 2 hours. Figure 2 As can be seen from (b), in Preparation Example 2, 45% Ni / Pr6O 11 -700℃ catalyst (45Ni-Pr) after reduction Pr6O 11 The NiO phase and NiO phase disappeared, and PrOx material and metallic Ni phase appeared (2θ = 44.5°, 51.8°, 76.4°). No phase transformation was observed after reduction in Comparative Example 3 (45% Ni / MgO-700℃ catalyst, 45Ni-Mg) and Comparative Example 4 (45% Ni / Al2O3-700℃ catalyst, 45Ni-Al). This is mainly because the extremely stable solid solution NiMgO2 or spinel NiAl2O4 phase is not easily reduced to metallic Ni. Compared with Preparation Example 2, Ni… 0 / Ni 2+ A ratio of 0 indicates poor catalytic effect.

[0108] Figure 2 -(c) is the preparation of Example 2 45% Ni / Pr6O 11 H2-TPR characterization of the catalyst at -700℃ (45Ni-Pr), the comparative example 3 (45% Ni / MgO) catalyst at -700℃ (45Ni-Mg), and the comparative example 4 (45% Ni / Al2O3) catalyst at -700℃ (45Ni-Al) were performed. Figure 2 As shown in (c), NiO itself exhibits two different hydrogen consumption peaks at 419℃ and 548℃, which are attributed to the reduction of small-sized NiO particles and large-volume NiO particles, respectively. Pr6O 11 It consumes hydrogen at 475°C, and reacts with Pr 4+ Restore to Pr n+ (n≤3) related, 45% Ni / Pr6O 11 The catalyst at -700℃ exhibits a hydrogen consumption peak at 425℃, indicating a close contact and strong interaction between NiO and PrOx. A shoulder peak appears at 310℃, which can be attributed to the reduction of NiO with weak interactions with PrOx or the reduction of small NiO particles. Furthermore, compared to the reduction of NiO, the 45% Ni / Pr6O... 11 The reduction of the -700℃ catalyst (45Ni-Pr) shifts to lower temperatures. Compared to the preparation of Comparative Example 3 (45% Ni / MgO-700℃ catalyst (45Ni-Mg)) and Comparative Example 4 (45% Ni / Al2O3-700℃ catalyst (45Ni-Al), the presence of spinel NiAl2O4 in the 45% Ni / Al2O3-700℃ catalyst (45Ni-Al) and solid solution NiMgO2 in the 45% Ni / MgO-700℃ catalyst (45Ni-Mg) leads to an excessively strong interaction between Ni and the support, which manifests as a hydrogen consumption peak exceeding 700℃ (e.g., 725℃).

[0109] Figure 2 -(d) is the preparation of Example 2 45% Ni / Pr6O 11 CO2-TPD characterization of the catalyst (45Ni-Pr) prepared at -700℃, the comparative example 3 (45% Ni / MgO-700℃ catalyst, 45Ni-Mg), and the comparative example 4 (45% Ni / Al2O3-700℃ catalyst, 45Ni-Al) after reduction at 400℃ for 2 h. From... Figure 2 As shown in (d), the 45% Ni / MgO-700℃ catalyst exhibits CO2 desorption peaks at 100-350℃, indicating the presence of weak to moderately strong basic sites on the surface of the 45% Ni / MgO-700℃ catalyst (45Ni-Mg). Conversely, the 5% Ni / Al2O3-700℃ catalyst (45Ni-Al) shows CO2 desorption peaks at weak (156℃), moderately strong (278℃ and 338℃), and strong (534℃) basic sites. 45% Ni / Pr6O 11 The -700℃ catalyst (45Ni-Pr) exhibits a broad and strong CO2 desorption peak in the range of 100-570℃, mainly originating from moderately strong basic sites.

[0110] from Figure 3 It can be seen that furfuryl alcohol can be completely converted in 12 hours using the comparative example 3 45% Ni / MgO-700℃ catalyst (45Ni-Mg), with the intermediate tetrahydrofurfuryl alcohol as the major product and a selectivity of 94.8%. Extending the reaction time to 60 hours, the major product is still the intermediate tetrahydrofurfuryl alcohol, with only a small amount of 1,5-pentanediol (5.0%) formed. The activity of the comparative example 3 45% Ni / MgO-700℃ catalyst (45Ni-Mg) is slightly higher than that of the comparative example 4 45% Ni / Al2O3-700℃ catalyst (45Ni-Al), indicating that both the comparative example 3 45% Ni / MgO-700℃ catalyst (45Ni-Mg) and the comparative example 4 45% Ni / Al2O3-700℃ catalyst (45Ni-Al) have very low ring-opening hydrogenolysis activity for tetrahydrofurfuryl alcohol. Furthermore, for the hydrogenation of the C=C bond on the furan ring of furfuryl alcohol, the activities of the catalysts prepared in Comparative Example 3 (45% Ni / MgO-700℃, 45Ni-Mg) and Comparative Example 4 (45% Ni / Al2O3-700℃, 45Ni-Al) were significantly lower than those of the catalyst prepared in Example 2 (45% Ni / Pr6O). 11 -700℃ catalyst (45Ni-Pr).

[0111] Figure 4 To prepare Example 2 45% Ni / Pr6O 11TEM and HRTEM images of the catalyst (45Ni-Pr) at -700℃, the comparative example 3 (45% Ni / MgO) at -700℃, and the comparative example 4 (45% Ni / Al2O3) at -700℃, after reduction at 400℃ for 2 hours. The 45% Ni / Al2O3 at -700℃ catalyst (45Ni-Al) showed a more uniform dispersion (see...). Figure 4 -(a)), and lattice fringes of NiO(200) (d=0.208nm) and NiAl2O4(311) (d=0.243nm) were observed in the HRTEM image of the 45% Ni / Al2O3-700℃ catalyst (45Ni-Al) (see Figure 4 -(d)). The solid solution structure of the 45% Ni / MgO-700℃ catalyst (45Ni-Mg) is in Figure 4 -(b) is very evident in the HRTEM images (see Figure 4 NiMgO2(111) crystal planes (d = 0.242 nm) were detected in (e)). Meanwhile, in 45% Ni / Pr6O... 11 TEM image of the catalyst (45Ni-Pr) at -700℃ (see...) Figure 4 -(c)) cannot combine Ni particles with PrOx (Pr6O) 11 After reduction, it is converted to PrOx) to distinguish them, but in the HRTEM image (see Figure 4 The lattice fringes of Ni(111) (0.203 nm) and Pr2O3(302) (0.313 nm) were clearly detected in (f), indicating that in 45% Ni / Pr6O 11 The catalyst (45Ni-Pr) at -700℃ contains PrOx (Pr6O) 11 After reduction, it transforms into PrOx.

[0112] Figure 5 (a) Preparation of Example 2 45% Ni / Pr6O 11 The N2 adsorption-desorption isotherms of the catalyst at -700℃ (45Ni-Pr), the comparative example 3 (45% Ni / MgO at -700℃, 45Ni-Mg), and the comparative example 4 (45% Ni / Al2O3 at -700℃, 45Ni-Al) all exhibited Type IV isotherms with hysteresis loops of type H1 or H3, indicating that all catalysts contain a mesoporous structure. Compared with the comparative example 3 (45% Ni / MgO at -700℃, 45Ni-Mg) and the comparative example 4 (45% Ni / Al2O3 at -700℃, 45Ni-Al), the catalyst of preparation example 2 (45% Ni / Pr6O) showed a different N2 adsorption-desorption isotherm. 11The -700℃ catalyst (45Ni-Pr) has a wider pore size (see...). Figure 5 (b)).

[0113] Figure 6 To prepare Example 2 45% Ni / Pr6O 11 -700℃ catalyst (45Ni-Pr) (see...) Figure 6 -(a)) Preparation of comparative example 345% Ni / MgO catalyst (45Ni-Mg) at 700℃ (see...) Figure 6 -(c)) and preparation of comparative example 4 45% Ni / Al2O3-700℃ catalyst (45Ni-Al) (see Figure 6 -(b) Elemental analysis of HAADF-STEM-EDX after reduction at 400℃ for 2 hours. Figure 6 The results showed that all catalysts exhibited a uniform distribution of elements, allowing all elements to be in close contact.

[0114] Preparation Example 3

[0115] The method of Preparation Example 1 is followed, except that the active metal is Cu, and the hydrogenolysis catalyst prepared has the following composition: 20% Cu / Pr6O 11 -700℃.

[0116] Preparation Example 4

[0117] The method of Preparation Example 1 is followed, except that the active metal is Co, and the hydrogenolysis catalyst prepared has the following composition: 20% Co / Pr6O. 11 -700℃.

[0118] Preparation Example 5

[0119] The method of Preparation Example 2 is the same, except that La2O3 is used as the support, and the hydrogenolysis catalyst prepared has the following composition: 45% Ni / La2O3-700℃.

[0120] Preparation Example 6

[0121] The method of Preparation Example 2 is the same, except that CeO2 is used as the support, and the hydrogenolysis catalyst prepared has the composition of 45% Ni / CeO2-700℃.

[0122] Preparation Example 7

[0123] The method of Preparation Example 2 is the same, except that Y2O3 is used as the support, and the hydrogenolysis catalyst prepared has the following composition: 45% Ni / Y2O3-700℃.

[0124] Preparation Example 8

[0125] The method was the same as in Example 1, except that the second-stage calcination temperature was 600°C, and the resulting hydrogenolysis catalyst had the following composition: 20% Ni / Pr6O. 11 -600℃.

[0126] Preparation Example 9

[0127] Following the method of Preparation Example 2, except that the second-stage calcination temperature was 750°C, and the resulting hydrogenolysis catalyst had the following composition: 20% Ni / Pr6O 11 -750℃.

[0128] Preparation Example 10

[0129] The method was the same as in Example 2, except that the second-stage calcination temperature was 800°C, and the resulting hydrogenolysis catalyst had the following composition: 20% Ni / Pr6O. 11 -800℃.

[0130] Preparation Example 11

[0131] The method was the same as in Preparation Example 2, except that the second-stage calcination temperature was 900°C, and the resulting hydrogenolysis catalyst had the following composition: 20% Ni / Pr6O. 11 -900℃.

[0132] Preparation Example 12

[0133] (1) According to Ni / (NiO+Pr6O 11 )= X Ni(NO3)2·6H2O and Pr(NO3)3·6H2O were dissolved in 20 mL of deionized water by weight ratio. Then, citric acid and metal salt (Ni+Pr) were added to the solution at a molar ratio of 1.5:1 under continuous stirring. Then, 12 g of glucose was stirred at room temperature for 4 h. Excess water was evaporated in a 90 °C water bath for 1 h until a viscous gel was formed.

[0134] (2) The obtained gel was dried at 120°C overnight. Finally, the dried gel was calcined in an air atmosphere in a muffle furnace at a first-stage calcination temperature of 400°C (from room temperature to 400°C at a heating rate of 4°C / min) for 5 h. Then, it was calcined in an air atmosphere in a muffle furnace at a second-stage calcination temperature of 720°C (from 400°C to the second-stage calcination temperature at a heating rate of 4°C / min) for another 5 h. The hydrogenolysis catalyst obtained had the following composition: 40% Ni / Pr6O 11 -720℃.

[0135] Preparation of Comparative Example 5

[0136] 45% Ni / Pr6O was prepared using a common co-precipitation method. 11The catalyst was prepared by weighing nickel nitrate (Ni(NO3)2·6H2O) and Pr(NO3)3·6H2O according to the above stoichiometric ratio, dissolving and dispersing them in 63 mL of deionized water, stirring for 30 min, and then adding 2 M NaOH solution dropwise until the pH of the solution reached 14. The mixture was stirred for 4 h, then transferred to a hydrothermal reactor and incubated at 150 °C for 48 h. Afterwards, the sample was filtered, washed with deionized water until the pH reached 7, and then dried in an oven at 80 °C for 12 h. Subsequently, the sample was calcined in air at 500 °C for 4 h to obtain the above catalyst. This catalyst is designated as: 45% Ni / Pr6O 11 -precipitation.

[0137] Preparation of Comparative Example 6

[0138] 45% Ni / Pr6O was prepared by impregnation method 11 The catalyst, prepared using the following method: First, a support Pr6O is prepared. 11 Praseodymium nitrate hexahydrate was dissolved in 20 mL of deionized water for 10 minutes with stirring, followed by the dropwise addition of 1 M sodium hydroxide solution until the pH of the solution reached 10.5. The slurry was stirred for 2 hours and then aged for 12 hours. Afterward, the sample was centrifuged and washed three times with deionized water (until pH = 7), and then dried in an oven at 100°C for 12 hours. The sample was then calcined in dry air at 500°C for 4 hours. The above-mentioned Pr6O support was then... 11 The mixture was mixed with nickel nitrate, stirred at room temperature for 2 hours, dried at 80°C overnight, and then calcined in dry air at 500°C for 4 hours. The catalyst was designated as Ni / Pr6O. 11 The catalyst described above is 45% Ni / Pr6O. 11 -Immersion.

[0139] The properties of the catalysts prepared in the above-mentioned examples and comparative examples are shown in Table 1.

[0140] Table 1

[0141]

[0142] Note: In Table 1, "-" indicates that no detection was performed.

[0143] The data in the table above show that when the second-stage calcination temperature is below 750℃, the catalyst has a high amount of medium-strong base and total base, which may be due to the presence of a large number of surface oxygen vacancies. When the second-stage calcination temperature reaches above 800℃, the amount of medium-strong base and total base decreases, resulting in poor hydrogenolysis performance of furfuryl alcohol. When the total proportion of weak base and medium-strong base is within a specific range, the hydrogenolysis performance of furfuryl alcohol is better.

[0144] The data in the table above shows that 45% Ni / Pr6O 11The -700℃ catalyst consumes more hydrogen than the 45% Ni / MgO-700℃ and 45% Ni / Al2O3-700℃ catalysts, indicating a lack of sufficient Ni. 0 The species dissociate adsorbed hydrogen molecules, resulting in poor hydrogenolysis performance of 45% Ni / MgO-700℃ catalyst and 45% Ni / Al2O3-700℃ catalyst in furfuryl alcohol.

[0145] Example 1

[0146] After catalyst reduction, the hydrogenolysis performance was directly tested under the following conditions: 0.5 g furfuryl alcohol, 9.5 g isopropanol, 170 °C, 6 MPa, for 72 h. The specific operating procedure is as follows:

[0147] After the catalyst is reduced, isopropanol is injected into a quartz tube under a hydrogen flow to protect the catalyst. The suspension is then transferred to an autoclave and mixed with furfuryl alcohol. The autoclave is then sealed and flushed three times with hydrogen to replace the air.

[0148] The autoclave was pressurized to the required H2 pressure at room temperature. Hydrogenation was initiated with stirring (900 rpm) once the set temperature was reached. After the reaction was stopped, the product was analyzed using a Techcomp GC-700Plus GC equipped with a flame ionization detector and a capillary column (DM-5, 30 m × 0.32 mm × 0.25 μm). The conversion of furfuryl alcohol and the product selectivity were calculated using a corrected normalization method. After the reaction, the suspension was separated by centrifugation, and the catalyst was washed several times with isopropanol to remove residual furfuryl alcohol and product. Subsequently, the recovered catalyst was mixed with fresh furfuryl alcohol for the next reaction cycle. No fresh catalyst was added during the entire cycle experiment. The test results are shown in Table 2.

[0149] Table 2

[0150]

[0151] Note: Other byproducts include 2-methylfuran, 2-methyltetrahydrofuran, 1,2-pentanediol, and tetrahydrofuran.

[0152] As can be seen from the results in the table above, compared with MgO and Al2O3 supports, the use of rare earth metals as supports in the hydrogenolysis catalyst provided by this invention is more conducive to the ring-opening hydrogenolysis of furfuryl alcohol and improves the selectivity of the products.

[0153] Example 2

[0154] The method was the same as in Example 1, except that the hydrogenolysis performance of furfuryl alcohol was tested over 60 hours. The test results are shown in Table 3.

[0155] Table 3

[0156]

[0157] Note: Other byproducts include 2-methylfuran, 2-methyltetrahydrofuran, 1,2-pentanediol, and tetrahydrofuran.

[0158] Example 3

[0159] The method of Example 1 was followed, except that 0.2 g furfuryl alcohol, 9.8 g isopropanol, 150 °C, 7 MPa were used to test the hydrogenolysis performance of furfuryl alcohol for 72 h. The test results are shown in Table 4.

[0160] Table 4

[0161]

[0162] Note: Other byproducts include 2-methylfuran, 2-methyltetrahydrofuran, 1,2-pentanediol, and tetrahydrofuran.

[0163] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A method for the hydrogenolysis of furfuryl alcohol to synthesize 1,5-pentanediol, wherein, The method includes: in the presence of hydrogen, contacting the reactant furfuryl alcohol and the hydrogenolysis catalyst to carry out a hydrogenolysis reaction; The hydrogenolysis catalyst comprises a support and an active metal, wherein the support is selected from Pr6O. 11 At least one of La2O3, CeO2 and Y2O3, wherein the active metal is selected from at least one of Cu, Co and Ni; After the hydrogenolysis catalyst was reduced at 400℃ for 2 hours, XPS characterization showed that the ratio of 0-valent to 2-valent species of the active metal was 0.1-2.

2. The method according to claim 1, wherein, After the hydrogenolysis catalyst was reduced at 400℃ for 2 hours, XPS characterization showed that the ratio of 0-valent species to divalent species of the active metal was 0.5-1.8, preferably 1.1-1.

3. Preferably, the total amount of medium-strong base and weak base in the hydrogenolysis catalyst accounts for 85-100% of the total base amount, and more preferably 94-96%.

3. The method according to claim 1 or 2, wherein, Based on the total weight of the hydrogenolysis catalyst, the content of the support is 55-90%, and the content of the active metal, calculated by element, is 10-45%. Preferably, based on the total weight of the hydrogenolysis catalyst, the content of the support is 55-70%, and the content of the active metal, calculated by element, is 30-45%.

4. The method according to claim 1 or 2, wherein, The carrier is Pr6O 11 ; Preferably, the active metal is Ni.

5. The method according to claim 1 or 2, wherein, The preparation method of the hydrogenolysis catalyst includes the following steps: (1) Mix the active metal precursor, the carrier precursor and the template agent, and carry out a sol-gel reaction to obtain a gel material; (2) The gel material described in step (1) is dried and calcined. The calcination includes a first-stage calcination and a second-stage calcination. The temperature of the first-stage calcination is 300-600℃, and the temperature of the second-stage calcination is 600-900℃.

6. The method according to claim 5, wherein, In step (1), the active metal precursor is selected from the salts of various active metals, preferably from at least one of the nitrates, basic carbonates, sulfates and chlorides of various active metals; Preferably, in step (1), the carrier precursor is selected from the metal salts of each carrier, and more preferably from at least one of the nitrates, basic carbonates, sulfates and chlorides of each carrier.

7. The method according to claim 5, wherein, In step (1), the template agent includes a first template agent and a second template agent; Preferably, the first template agent is an organic acid and / or an inorganic acid, preferably selected from at least one of tartaric acid, acetic acid and citric acid; Preferably, the second template agent is a carbohydrate compound, preferably selected from at least one of fructose, sucrose, and glucose; Preferably, the molar ratio of the first template agent to the active metal precursor is 0.1-5:1, more preferably 0.5-3:1; Preferably, the molar ratio of the second template agent to the active metal precursor is 0.1-5:1, more preferably 0.5-3:

1.

8. The method according to claim 5, wherein, In step (1), the conditions for the sol-gel reaction include: a temperature of 70-98℃ and a time of 0.5-2h; Preferably, in step (2), the conditions for the first-stage roasting include: the temperature of the first-stage roasting is 300-500℃, the time is 1-6h, and the heating rate is 2-7℃ / min; Preferably, in step (2), the conditions for the two-stage roasting include: the temperature of the two-stage roasting is 650-730℃, the time is 3-7h, and the heating rate is 2-7℃ / min.

9. The method according to claim 1 or 2, wherein, The conditions for the hydrogenolysis reaction include: a reaction temperature of 140-210℃, a reaction hydrogen pressure of 4-7MPa, a reaction time of 2-72h, and the amount of the hydrogenolysis catalyst used is 0.2-1g compared to 1g of the reaction raw material furfuryl alcohol. Preferably, the conditions for the hydrogenolysis reaction include: a reaction temperature of 150-190℃, a hydrogen pressure of 5-7MPa, a reaction time of 48-72h, and the amount of the hydrogenolysis catalyst used is 0.3-0.5g compared to 1g of furfuryl alcohol as a reaction feedstock. Preferably, the hydrogenolysis reaction further includes being carried out in the presence of a solvent selected from at least one of isopropanol, ethanol, and 1,4-dioxane; Preferably, the amount of solvent used is 10-100g compared to 1g of furfuryl alcohol, a reactant.

10. The method according to claim 1 or 2, wherein, The hydrogenolysis reaction further includes: reducing the hydrogenolysis catalyst before the hydrogenolysis reaction; Preferably, the conditions for the reduction treatment include: a temperature of 300-500℃ and a time of 1-4h.

Citation Information

Patent Citations

  • Application of nickel-containing catalyst in preparation of 1,5-pentanediol from furfural

    CN114073967A